PENERAPAN TEKNOLOGI MESIN PENGUPAS BAWANG DALAM PENINGKATAN USAHA BAWANG GORENG “BAGOR KRIUK BTN” - Husman Amat Muni; Adhe Anggri; Sugiyarto Sugiyarto (Jurnal Pengabdian Masyarakat Polmanbabel, 2023)
The process of making fried onions is carried out in several stages until they become fried onions that are ready to be consumed, starting from peeling the onion skin, slicing, frying, slicing, and packing. From the results of a survey conducted on service partners, the process of peeling onion skins is still manual, namely peeling it using a knife one by one. It takes approximately 4 hours to peel 15 Kg of raw shallots which is done by 2 employees, and the process takes a lot of time. In order to increase the production of shallots, a shallot peeling machine was developed to speed up the stripping process. Partners will receive appropriate technology in the form of a shallot peeler and training in the process of using the machine and maintaining the machine. In addition, a monitoring and evaluation process is also carried out to measure the level of success and constraints on the machines that have been used by partners. After the development of the shallot peeling machine was developed, the partner's production productivity increased, the machine functioned properly and was able to peel as much as 5 kg of shallot skin in 10 minutes or 30 kg/hour.